ANALYSIS OF COMPLICATIONS DURING PROSTHESIS WITH INDIRECT RESTORATIONS FOR FRONT TEETH - O.M. Stupytska; V.V. Chamata; K.I. Pavlenko (Ukrainian Medical Stomatological Academy, 2017)
Nowadays the method of teeth restoration with veneers is a leader of the defects of the front teeth removal due to its constructions which are non-invasive and have a good aesthetic. However, such high-precision restorations have a failure rate and complications that are detailed below in the article. The outcomes of porcelain veneers have been studied during a long period. A recent meta-analysis found the summary cumulative survival was 95% at 5 years, 93% at 10 years and 83% at 20 years. The change of the colour, non-satisfaction with restoration shade, postoperative sensitivity, secondary caries, bad marginal adaptation, marginal discoloration, fractures were common complications for teeth restored with porcelain composite veneers. Tooth preparation causes the formation of smear layer, which is removed or modified by the adhesive system. In order to achieve a stable bonded interface to dental tissues, adhesive systems have to include three crucial application steps, i.e. etching, priming and bonding. Etching with an acidic solution, such as 35-37% orthophosphoric acid, demineralizes both enamel and dentin surfaces producing roughness and increasing their surface of free energy. With priming, wettability of the tooth surface is increased and hydrophilic monomers and solvents in the primer composition provide substitution for the water on the substrate with the resin monomers. In the bonding step, after penetration and polymerization of monomers onto the etched enamel surface or exposed collagen network in dentin, micromechanical interlocking occurs. Self-etching refers to the acid etching and priming of dentin at the same time with acidic monomers without rinsing resulting in a modified smear layer to form the hybrid layer between the dentin and resin, whereas etch-and-rinse approach refers to acid etching of the enamel/dentin surfaces and after this treatment the surfaces are rinsed in order to eliminate the smear layer and then primer, bond and resin application to form the hybrid layer. Biodegradation of the non-encapsulated collagen fibrils are the main cause of degradation of the hybrid layer and thus of adhesion between the tooth and the restoration. Biodegradation occurs in the hybrid layer and involves consecutive processes. The first stage of biodegradation begins when dentin is acid-etched for removal of the smear layer, exposing the underlying collagen fibril matrix for hybrid layer formation. The second stage involves extraction of the resins that had infiltrated the dentin matrix through water-filled voids within the hybrid layer. The third stage involves enzymatic attack of the exposed collagen fibrils, leading to depletion of collagen fibrils. It has been demonstrated that exposure of collagen matrix by acid etching activates matrix metalloproteinases (MMPs), that are known to cause collagenolysis in the presence of water. To ensure the retention is achieved, good marginal fit, tightness of indirect restorations also largely depends on luting cement. Materials for fixation must be indifferent to the tissues, do not cause the irritation of dentin and pulp, provide strong bond strength results and adhesion, to keep a constant volume and does not deform during curing, get a coefficient of thermal expansion close to the coefficient of expansion of tissues. Marginal adaptation which determined by the shrinkage of the material - it should be minimal, and it also depends on film thickness of luting cement. The durability of veneers depends on many factors as choosing a design, technology of its manufacture, preparation, and adhesive fixation.